2005
DOI: 10.1158/0008-5472.can-05-0043
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analysis Identifies NDRG2 as a Candidate Tumor Suppressor Gene Frequently Inactivated in Clinically Aggressive Meningioma

Abstract: Although meningiomas are common central nervous system tumors, little is known about the genetic events responsible for malignant progression. In this study, we employed gene expression profiling to identify transcripts whose expression was lost in anaplastic (WHO grade III) versus benign (WHO grade I) meningioma. Approximately 40% of genes downregulated in anaplastic meningioma were localized to chromosomes 1p and 14q. One specific gene located at 14q11.2, NDRG2, was consistently down-regulated in grade III m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
145
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 19 publications
8
145
2
7
Order By: Relevance
“…In several studies, low-expression of NDRG2 was found in multiple types of cancers or cells (Lusis et al, 2005;Lorentzen et al, 2007;Lee et al, 2008;Zhao et al, 2008;Shi et al, 2009). For example, NDRG2 was highly expressed in normal colonic mucosa and colonic adenomatous tissues, but was expressed at lower levels in all invasive cancer tissues .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, low-expression of NDRG2 was found in multiple types of cancers or cells (Lusis et al, 2005;Lorentzen et al, 2007;Lee et al, 2008;Zhao et al, 2008;Shi et al, 2009). For example, NDRG2 was highly expressed in normal colonic mucosa and colonic adenomatous tissues, but was expressed at lower levels in all invasive cancer tissues .…”
Section: Discussionmentioning
confidence: 99%
“…The members of this family have different tissue expression patterns, indicating that they may play distinct roles, but some exhibit similarities in either expression regulation or biological functions. Importantly, human NDRG2 was proposed to be a candidate tumor suppressor gene, due to its reduced expression in many cancer tissues including meningioma (Lusis et al, 2005), lung cancer, pancreatic cancer, and liver cancer (Hu et al, 2004), as well as its ability to inhibit proliferation in certain cancer cells like glioblastoma (Deng et al, 2003). Recently, it has been shown that NDRG2 can regulate cytokine signaling in breast cancer cells through the regulation of SOCS1 expression, which is capable of modulating STAT3 signaling .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that NDRG2 expression is down-regulated in a variety of carcinomas including liver cancer, pancreatic cancer (Hu et al, 2004), and meningioma (Lusis et al, 2005), and it is also associated with cell growth, differentiation, and apoptosis (Choi et al, 2007). In addition, NDRG2 expression in breast cancer cells has been shown to inhibit STAT3 activation via SOCS1 induction, followed by a decrease in cell proliferation .…”
mentioning
confidence: 99%
“…10 Interestingly, in our study, all except two cases with the complete loss of chromosome 14 also displayed del(1p36) in the ancestral tumour cell clone (Table 1) and these latter patients included the two cases who had relapsed. Previous studies 1,11,36 have defined a few regions (eg, 14q24.3-q32.33 and 14q11.2) as critical regions in chromosome 14 where candidate genes involved in determining the clinical behaviour of meningiomas could be localized. In this study, we were not able to identify small interstitial deletions, mutations or epigenetic silencing phenomena involving these regions, in the series of patients analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the inactivation of NDRG2 gene, localized at the chromosome 14q11.2 region, has been recently reported in histologically malignant meningiomas. 11 Array-based comparative genomic hybridization (a-CGH) is a powerful technique developed to detect copy number variation (CNV) of specific DNA sequences with higher resolution 12 than the conventional approaches -for example, conventional karyotyping and metaphase CGH-. 2,13 -17 This assay is based on a competitive hybridization between tumour and control DNA, labelled with different fluorochromes, to previously defined chromosome sequences inserted into well-characterized genomic clones -for example, bacterial (BAC) or P1-derived artificial chromosomes (PAC) -spotted onto glass slides 18 -20 with a resolution of around between 100 Kb and 1 Mb.…”
Section: Introductionmentioning
confidence: 99%